Icariin Augments Bone Formation and Reverses the Phenotypes of Osteoprotegerin-Deficient Mice through the Activation of Wnt/β-Catenin-BMP Signaling. (4th November 2013) - Li, Xiao-Feng; Xu, Hao; Zhao, Yong-Jian; Tang, De-Zhi; Xu, Guo-Hua; Holz, Jonathan; Wang, Jing; Cheng, Shao-Dan; Shi, Qi; Wang, Yong-Jun
Abstract : Icariin has been mostly reported to enhance bone fracture healing and treat postmenopausal osteoporosis in ovariectomized animal model. As another novel animal model of osteoporosis, there is few publication about the effect of Icariin on osteoprotegerin-deficient mice. Therefore, the goal of this study is to find the effect on bone formation and underlying mechanisms of Icariin in osteoprotegerin (OPG) knockout (KO) mice. We found that Icariin significantly stimulated new bone formation after local injection over the surface of calvaria at the dose of 5 mg/kg per day. With this dose, Icariin was also capable of significantly reversing OPG-deficient-induced bone loss and bone strength reduction. Real-time PCR analysis showed that Icariin significantly upregulated the expression of BMP2, BMP4, RUNX2, OC, Wnt1, and Wnt3a in OPG KO mice. Icariin also significantly increased the expression of AXIN2, DKK1, TCF1, and LEF1, which are the direct target genes of β -catenin signaling. The in vitro studies showed that Icariin induced osteoblast differentiation through the activation of Wnt/ β -catenin-BMP signaling by in vitro deletion of the β -catenin gene using β -catenin fx/fx mice. Together, our findings demonstrate that Icariin significantly reverses the phenotypes of OPG-deficient mice through the activation of Wnt/ β -catenin-BMP signaling.